Long term use of oral contraceptives comprising synthetic estrogens induces an excessive breast cancer risk in BRCA mutation carrier women: a meta-analysis - Hongling Peng; Xiaorong Qi; Qiao Wang (IMR Press, 2022)
Background: The relationship between oral contraceptive (OC) use and breast cancer risk is highly debated. Recent publications support a slight increase in overall breast cancer risk among OC user women, in particular among the current users. Women with inherited BRCA1 (Breast cancer type 1) or BRCA2 (Breast cancer type 2) gene mutations are at increased risk of breast and ovarian cancers, which is often mistakenly attributed to their elevated endogenous estrogen levels. The aim of presented meta-analysis was to assess the effects of OC use on breast cancer risk in BRCA mutation carrier women with minimal bias. Methods: A systematic search strategy was used to identify relevant studies, Stata (version 15) was used for meta-analysis. Results: Individual datasets from 13 studies totaling 20,202 patients were analyzed. The combined results showed no significant increase in risk of breast cancer in BRCA mutation carriers who had ever used oral contraceptive (HR = 1.09, 95% CI: 0.71-1.69 among BRCA1 mutation carriers and HR = 1.19, 95% CI: 0.73-1.95 among BRCA2 mutation carriers, respectively). However, in correlation with long-term (>5 years) OC users, the breast cancer risk was significantly increased in both BRCA1 mutation carriers (HR = 1.39, 95% CI: 1.19-1.60) and BRCA1 mutation carriers (HR = 1.61, 95% CI: 1.25-1.96). Conclusion: The presented results indicate that in BRCA mutation carriers women who have defective liganded activation of estrogen receptors (ERs), the use of synthetic estrogens means an additive factor for ER deregulation further increasing the risk for breast cancer. Long term OC use in BRCA mutation carriers results in a significantly increased risk for breast cancer by exhausting the compensatory genome defending process.